In vivo assessment of acute and subchronic toxicity of Nanochitin in experimental animals - Cha, Nguyen Thi; Ha, Ho Phu; Thanh, Nguyen Tien; Hung, Bui Tien; Van Anh, Pham Thi; Ha, Nguyen Thi Thanh; Quang, Trinh Vinh; Hang, Dinh Thi Thu (Tạp chí Nghiên cứu Y học, 2025)
This study aimed to evaluate the safety of Nanochitin through oral administration in experimental animals. The acute toxicity was determined in mice at ascending doses and the subchronic toxicity was evaluated in rats with oral doses of 15.6 mg/kg b.w/day and 46.8 mg/kg b.w/day for 30 days. As a result, in the course of the acute toxicity test, Nanochitin at the highest dose of 750 mg/kg did not express acute toxicity in mice. Along with the subchronic toxicity test, Nanochitin had no deleterious effect on hematological parameters, hepato-renal functions, macroscopic and microscopic images of the livers and kidneys of rats. In conclusion, Nanochitin does not appear to produce acute and subchronic toxicities in experimental animals.